Fellowship in Museum Practice, Smithsonian Institution, USA (Smithsonian American Art Museum) (6 months) - Stylianou-Lambert, Theopisti (My University, 2026)
Fellowship in Museum Practice, Smithsonian Institution, USA (Smithsonian American Art Museum) (6 months)
Keywords: Social sciences